(untitled) (Journal of Medical & Health Sciences Review, 2025)
ABSTRACT Background: Internal medicine serves as the foundation of medical practice, encompassing the diagnosis, treatment, and prevention of a wide range of diseases affecting internal organs and systems. Understanding its complexities, challenges, and transformative potential is crucial for advancing medical care. Objectives: This paper aims to explore the historical evolution, current state, and future perspectives of internal medicine, emphasizing its multifaceted nature and the integration of medical knowledge and clinical skills in patient care. Methods: A comprehensive review of literature and medical practices is conducted to analyze the principles of diagnostic reasoning, therapeutic interventions, and advancements in patient-centered care. The study further examines the role of interdisciplinary collaboration and technological innovations in shaping the future of internal medicine. Results: Findings highlight the dynamic nature of internal medicine, demonstrating how medical knowledge, clinical expertise, and evolving technologies contribute to improved patient outcomes. The importance of interdisciplinary teamwork, innovative therapeutic approaches, and patient-centered techniques in enhancing healthcare delivery is underscored. Conclusion: Internal medicine is a continuously evolving discipline that requires adaptability, collaboration, and innovation. By understanding its core principles and future directions, medical professionals can enhance their practice and contribute to improved healthcare systems. This paper encourages continuous learning, professional growth, and the pursuit of excellence in patient care.